The innovative competitive advantage : a case study of two pioneering companies - Whalen, Elizabeth A., (SAGE Business Cases., 2017)
This case study examines the use of innovative strategies to create a competitive advantage by exploring two different restaurants. The restaurants differ in their methodology, one focusing on marketing promotions and the other focusing on operations management. However, the two concepts represent the range of potential innovative strategies. The Little Bay Restaurant in London ran a month long promotion during the height of the economic recession of 2009 in which customers set their own prices for the meals they bought. This promotional strategy allowed customers to decide the value of their meal, while the business was able to attract new customers even during hard economic times. The Eatsa restaurant in San Francisco took a different approach. It focused on an innovative operational process via advanced technology. With the increased costs of labor due to a raise in the local minimum wage, the owner of the new Eatsa concept decided to co-create value with the customer by eliminating front of the house employees using do-it-yourself procedures.